Requiem of Olympic ethics and sports’ independence: A panel-data socio-cultural analysis - Fabio Zagonari (PLoS ONE, 2025)
This paper suggests a theoretical model (a production function) and an empirical model (Stochastic Frontier Analysis) to empirically evaluate the main impacts of socio-cultural contexts on the effectiveness of some sport policies and to address some main methodological problems of sport sociology. As for methods, I identified 2 governmental ethics to and through sport (national pride NP, social cohesion SC), by measuring achievements in terms of alternative indexes based on Olympic medals (gold, total) from 1994 to 2024. I applied panel-data, by focusing on 4 alternative estimations (individual and collective variables for both NP and SC). I introduced 2 sport policies (a quantitative policy aimed at SC, a qualitative policy aimed at NP), by distinguishing cultural approaches to body in terms of 5 different secular ethics (Aristotle, Husserl, Deleuze, Heidegger, Descartes) and 5 different religious ethics (Buddhism, Christianism, Hinduism, Islam, Judaism). I referred to income level and income inequality (i.e., GDP and Gini index), to depict alternative social contexts. I applied country dummies, to represent alternative historical and institutional contexts. As for results, if governments pursue SC, there is significant consonance with more communitarian religions and dissonance with more individualistic religions (to a greater extent at a collective level), whereas religions do not affect the effectiveness of sport policies if governments pursue NP. If governments pursue NP, there is significant consonance with secular body approaches deemphasising mind over body (at an individual level only), whereas if governments pursue SC, there is significant consonance with Deleuze, Heidegger and Descartes and dissonance with Husserl (to a smaller extent at a collective level). In summary, this paper empirically highlights the social and cultural contexts affecting some sport policies, by providing a quantitative methodology to identify groups of countries with institutional or historical peculiarities, to be studied by sport sociology with complementary qualitative methodologies.